Pendapatan Murabahah, Mudharabah, dan Musyarakah Terhadap Profitabilitas Bank Dengan NPF Sebagai Variabel Moderating - Fadilah Zaidan (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
This study aims to determine the effect of Murabahah income, mudharabah income, musyarakah income, and NPF to profitability in sharia commercial banks. The result of this research shows that partially Murabahah income not has an effect on Profitability. This is evidenced by the value of t count of 1,334 and the value of ttable 2.004 (1,334 < 2.004) with significance of 0.188 > 0.05. Where as mudharabah income not has an effect on Profitability. It is proved by tcount of 1,674 and ttable value 2.004 (1,674 < 2,004) and significance level of 0.100 > 0,05. And musyarakah income has a negative effect on profitability. It is proved by tcount of -3,247 and ttable value -2.004 (-3,247 < -2,004) and significance level of 0.002 < 0,05. Also NPF has a negative effect on profitability. It is proves by tcount of -8,204 and ttable value -2.004 (-8,204 < 2,004) and significance level of 0.000 < 0,05. As simultaneously Murabahah income, mudharabah income, musyarakah income, and NPF effect on Profitability. This is evidenced by the value of Fhitung of 27.225 and Ftable value of 2.54 (27.225 > 2.54) and a significance level of 0.000 < 0.05.